Enantioselective Synthesis of Putative Lipiarmycin Aglycon Related to Fidaxomicin/Tiacumicin B1. Issue 6 (24th November 2014) - Erb, William; Grassot, Jean‐Marie; Linder, David; Neuville, Luc; Zhu, Jieping
Abstract: An enantioselective synthesis of a putative lipiarmycin aglycon was accomplished and features: 1) Brown′s enantioselective alkoxyallylboration and allylation of aldehydes, 2) chain elongation by iterative Horner–Wadsworth–Emmons olefination, 3) Evans' aldol reaction and 4) an ene‐diene ring‐closing metathesis. A neighboring‐group‐assisted chemoselective reductive desilylation was uncovered in this study and was instrumental to the realization of the present synthesis. Abstract : Chain gang : In the synthesis of the title compound, the ene‐diene ring‐closing metathesis was used for the formation of the 18‐membered macrolactone and the stereogenic centers of the molecule were installed by Brown's alkoxyallylboration, allylation, and an Evans aldol reaction, while iterative Horner–Wadsworth–Emmons reactions were used for chain elongation.